2019
DOI: 10.1371/journal.pone.0222798
|View full text |Cite
|
Sign up to set email alerts
|

The negative effects of short-term extreme thermal events on the seagrass Posidonia oceanica are exacerbated by ammonium additions

Abstract: Global warming is increasingly affecting our biosphere. However, in addition to global warming, a panoply of local stressors caused by human activities is having a profound impact on our environment. The risk that these local stressors could modify the response of organisms to global warming has attracted interest and fostered research on their combined effect, especially with a view to identifying potential synergies. In coastal areas, where human activities are heavily concentrated, this scenario is particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 104 publications
(125 reference statements)
2
24
0
Order By: Relevance
“…These results are in accordance with other studies with temperate species that showed no interactive effects on fluorescence parameters or growth (Bintz et al, 2003;Moreno-Marín et al, 2018;Ontoria et al, 2019b). However, in some studies significant interactions were found for yield, growth (Kaldy, 2014;Mvungi and Pillay, 2019;Ontoria et al, 2019a), or photosynthetic rate, as well as gross production rates (Egea et al, 2018;Moreno-Marín et al, 2018). Comparison among studies is difficult due to the variable traits measured; and care must be taken when comparing results that differ in exposure period, the intensity of the stressors (e.g., nutrient concentration used), or even the different geographical areas of the species, as all these factors, among others, might affects the plasticity of seagrass traits.…”
Section: Combined Effect Of Different Drivers: Stressors Do Not Act Asupporting
confidence: 92%
“…These results are in accordance with other studies with temperate species that showed no interactive effects on fluorescence parameters or growth (Bintz et al, 2003;Moreno-Marín et al, 2018;Ontoria et al, 2019b). However, in some studies significant interactions were found for yield, growth (Kaldy, 2014;Mvungi and Pillay, 2019;Ontoria et al, 2019a), or photosynthetic rate, as well as gross production rates (Egea et al, 2018;Moreno-Marín et al, 2018). Comparison among studies is difficult due to the variable traits measured; and care must be taken when comparing results that differ in exposure period, the intensity of the stressors (e.g., nutrient concentration used), or even the different geographical areas of the species, as all these factors, among others, might affects the plasticity of seagrass traits.…”
Section: Combined Effect Of Different Drivers: Stressors Do Not Act Asupporting
confidence: 92%
“…Optimum growth temperature for this temperate species range from 11.5 to 26 • C (Olsen et al, 2012). However, this optimal range probably depends on other co-occurring environmental factors, such as nutrient availability, leaf senescence and nutrient partitioning within plant tissues (Ontoria et al, 2019a). Indeed, photochemical efficiency and carbohydrate reserves of OL plants were not affected by warming in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Few multi-factorial experiments have been performed on P. oceanica, including some assessing nutrient (ammonium) input and temperature (Gera et al, 2013;Ontoria et al, 2019a). In these studies, different levels of synergism have been found between stress factors, influencing negatively the survival, photosynthesis and plant growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When slow‐growing persistent seagrass species are disturbed, they can take decades to recover (O'Brien et al, 2018). Any recovery may also be inhibited by ongoing heating and recurrent MHWs (Marbà & Duarte, 2009) as well as synergistic pressures, such as heat stress and nutrients (Ontario, Cuesta‐Gracia, Ruiz, Romero, & Pérez, 2019). Following the 2011 WA MHW, Shark Bay was subjected to above average SST for several years (Gilmour et al, 2019), which may have impeded recovery rates of persistent seagrasses, prolonging the impacts associated with the initial loss.…”
Section: Discussionmentioning
confidence: 99%